(untitled) (The Review of Diabetic Studies, 2025)
Cervical spine injuries (CSIs) pose significant risks due to their potential for catastrophic neurological consequences. Paramedics play a crucial role in the prehospital management of suspected CSIs, as their decisions and actions can significantly impact patient outcomes. This review provides a comprehensive synthesis of current evidence and practices related to the prehospital management of suspected CSIs from a paramedic perspective. The epidemiology of CSIs is discussed, highlighting the predominance of these injuries in young adult males and the increasing incidence among the elderly population. The pathophysiology of CSIs is explored, emphasizing the importance of minimizing secondary injury through early immobilization and careful patient handling. The paramedic’s role and responsibilities in assessing and managing suspected CSIs are outlined, including the use of clinical decision tools and immobilization techniques. Airway management in the context of suspected CSIs is a critical challenge for paramedics, requiring a balance between maintaining airway patency and minimizing cervical spine movement. Pain and sedation management is also discussed, considering the need to provide effective analgesia while preserving neurological assessment integrity. Extrication and transport considerations are reviewed, focusing on safe patient movement techniques and the decision between air and ground transport. Finally, recommendations for practice improvement are provided, summarizing best practices supported by current evidence, identifying areas requiring further research, and emphasizing the importance of interprofessional collaboration between paramedics, nurses, and physicians in optimizing patient care.